A qualitative investigation into crowdfunding framework as a source of financing for waqf land development - Hapsari, Meri Indri; Mohd Thas Thaker, Mohamed Asmy; Omar Mohamad, Mustafa; Duasa, Jarita (Emerald, 2022)
Purpose –This paper aims to inquire about the opinions and recommendations of various experts on the crowdfunding waqf model (CWM), particularly in terms of its suitability, applicability and prospect in the market.